Evolution of cooperation on temporal networks - Aming Li (Nature Portfolio, 2020)
Population structure enables emergence of cooperation among individuals, but the impact of the dynamic nature of real interaction networks is not understood. Here, the authors study the evolution of cooperation on temporal networks and find that temporality enhances the evolution of cooperation.